Direct oxidative Ammonia-Ammonium salt leaching of sphalerite concentrate from the Gamsberg Mine and study of the catalytic effect of Cu(II) on Zinc extraction - Shabalala, Sanele (Department of Chemical Engineering, 2026)
The feasibility of using ammonia-ammonium salts to selectively leach Zn over Fe from Gamsberg sphalerite flotation concentrate under moderate temperatures and atmospheric pressure was investigated in stirred tank reactors. This approach is suggested as an alternative primary method for extracting Zn from sphalerite concentrates that are not environmentally friendly to process with conventional sulfuric acid leaching techniques. The analysed concentrate consists of 43.7 wt.% Zn, 0.17 wt.% Cu, 8.3 wt.% Fe, 29.1 wt.% S, 3 wt.% Pb, 2.4 wt.% Mn, and 5.4 wt.% Si, with mineralogical components including sphalerite (81.2 wt.%), galena (3.2 wt.%), quartz (9.3 wt.%), mica (2 wt.%), clinochlore (1.7 wt.%), and plagioclase (2.6 wt.%). This study begins with preliminary tests to evaluate the effectiveness of ammonium salts (chloride, sulphate, and carbonate) and to examine the catalytic effect of Cu(II) ions on the direct selective leaching of Zn over Fe from the concentrate, using oxygen and compressed air as the oxidative mediums. Ammonium chloride was the most effective salt for selectively leaching Zn over Fe, and the addition of Cu(II) ions improved Zn extraction in an oxygen medium. Ammonium chloride was then used to optimise parameters such as temperature, total ammonia concentration, pulp density and Cu(II) concentration for Zn extraction. The optimal conditions found were 6 mol/L [NH3]T (NH3/NH4+ ratio of 1), ~0.38 g/L Cu(II) concentration, 2% w/v pulp density, a leaching temperature of 55°C, agitation of 500 rmp in oxygen for 72 hours. Under these conditions, a Zn extraction efficiency of 99.5% was achieved. The rate of Zn extraction increased with rising temperatures (35–55°C), but at higher temperatures (75°C), NH3 evaporation impacted the initial extraction rates. The Zn extraction rates also increased with an increase in total ammonia concentration and Cu(II) concentration but decreased with an increase in pulp density. Initial slope analysis was used to characterize the leaching kinetics for each particle, providing good linear fits (R2 > 0.99) across all temperatures, ammonia concentrations, Cu(II) concentrations, and oxygen partial pressures. The activation energy was calculated to be 41.6 kJ/mol using the Arrhenius equation, suggesting that the leaching process was controlled by a surface chemical reaction and was highly sensitive to temperature. The shrinking core models were plotted under optimal conditions, confirming that the leaching process was governed by surface chemical reaction control. The reaction order for total ammonia concentration, Cu(II) concentration, and oxygen partial pressure were determined to be 0.22, 0.079, and 0.46, respectively. Due to its high volatility, NH3 evaporates rapidly. The concentration of total evaporated ammonia was determined through spectrophotometric analysis by measuring the total ammonia accumulated in scrubber bottles from the reactor after a set leaching period. The concentration of evaporated NH3 was found to increase with longer leaching times, higher temperatures, and greater initial total ammonia concentrations, with the highest evaporation observed at 75°C after 3 days of leaching. For optimal reagent conservation, a leaching temperature of 55°C is recommended for ammonia leaching of sphalerite from the Gamsberg mine.